Universal Service Obligations in Developing Countries - Estache, Antonio; Laffont, Jean-Jacques; Xinzhu Zhang (World Bank, Washington, D.C., 2013)
This paper develops a model to analyze the impacts of asymmetric information on optimal universal, service policy in the public utilities of developing countries. Optimal universal service policy is implemented using two regulatory instruments: pricing and network investment. Under discriminatory pricing asymmetric information leads to a higher price, and smaller network in the rural area, than under full information. Under uniform pricing, the price is also lower but the network is even smaller. In addition, under both pricing regimes, not only the firm, but also taxpayers have incentives to collude with the regulator.